2014
DOI: 10.1007/s00405-014-2996-4
|View full text |Cite
|
Sign up to set email alerts
|

Jugular bulb abnormalities in patients with Meniere’s disease using high-resolution computed tomography

Abstract: Temporal bone abnormalities such as hypoplasia of the vestibular aqueduct or hypopneumatization of the mastoid have been described in Meniere's disease (MD). Jugular bulb abnormalities (JBA) are one of the most common temporal bone abnormalities. The aim of this study was to evaluate the frequency of JBA in MD. Radiological data obtained by temporal bone high-resolution computed tomography of 200 ears of 167 MD patients (MD group) and 218 ears of 109 patients with normal inner ear function (control group) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 17 publications
3
28
0
Order By: Relevance
“…The prevalence of jugular bulb abnormalities increases during the first four decades of life and stabilizes thereafter 9. While it is not possible accurately to identify what percentage of diverticula are symptomatic (and it is recognized that many will be asymptomatic6), they have been described in association with pulsatile tinnitus and other symptoms such as vertigo and hearing loss in a number of case series 1 2 6 10–12. Patients tend to be >50 years of age at presentation 10 11…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The prevalence of jugular bulb abnormalities increases during the first four decades of life and stabilizes thereafter 9. While it is not possible accurately to identify what percentage of diverticula are symptomatic (and it is recognized that many will be asymptomatic6), they have been described in association with pulsatile tinnitus and other symptoms such as vertigo and hearing loss in a number of case series 1 2 6 10–12. Patients tend to be >50 years of age at presentation 10 11…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis can be made with MR venography, but the optimal imaging tool is probably a combination of CT venography and skull base CT, allowing identification of the relationship to adjacent structures 2 10. The surgical treatment of JBD involves mastoidectomy and impaction of bone wax 4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Several studies analyzing the temporal bone imaging 20 or anatomy in MD patients have found consistent alterations in the arrangement of the sigmoid sinus, anteriorly or medially displaced, and jugular bulb abnormalities. According to Redfern et al 21 and Park et al 22 there is a higher frequency of jugular bulb abnormalities in patients with MD than in patients without inner ear symptoms, particularly, the mediolateral and anteroposterior position of the jugular bulb determines encroachment of the surrounding structures. Authors postulated that abnormal position contributes to MD development and that temporal bones of MD patients might be constituted anatomically different, carrying predisposing factors for the development of clinically apparent MD.…”
Section: Discussionmentioning
confidence: 99%
“…Both studies show an increase of jugular bulb abnormalities in Ménière's disease compared with the asymptomatic side 1 or a control group. 2 This approach provides a new means to understand Ménière's disease physiopathology. In addition, the findings have clinical consequences that are worth knowing by the surgeon.…”
mentioning
confidence: 99%